Sistem Pendidikan Sekolah Dan Kurikulum Berbasis Keterpaduan - Mubarok, H. E.S.; Badrusalam, Deden; Aryani, Wiwik Dyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to identify the curriculum used by the Yaspida Sukabumi Islamic College. This study uses a qualitative approach using descriptive methods. The data collection technique uses in-depth interviews, observation and documentation studies. The research results show that the integrated curriculum provides learning opportunities and possibilities for students. The integration-based curriculum in Yaspida Sukabumi Islamic College is a curriculum that integrates the curriculum of Islamic boarding schools and schools with integrated curriculum components, community-based curriculum, competency-based curriculum, and worship practice-based curriculum